Sub-National Government's Risk Premia : Does Fiscal Performance Matter? - Sola, Sergio (IMF Working Papers; Working Paper, 2015)
This paper examines the determinants of sub-national governments risk premia using secondary market data for U.S., Canada, Australia and Germany. It finds that, as for central governments, fiscal fundamentals matter in the pricing of risk premia, and sub-national governments with higher public debt and larger deficits pay higher premia. However, this relationship is not uniform across countries. Market pricing mechanisms are less effective in presence of explicit or implicit guarantees from the central government. Specifically, we show that in pricing risk premia of sub-national governments, markets are less responsive to fiscal fundamental when sub-national governments depend on high transfers from the central government, id est, when there is some form of implicit guarantee from the center. Using primary market data, the paper also looks at whether transfer dependency from the central government influences sub-national governments' incentive to access markets. We show that high transfer dependency lowers the probability of sub-national governments to borrow on capital markets.